Highly conserved DNA sequence present in small plasmids from Selenomonas ruminantium - Fliegerova, K; Pazoutova, S; Pristas, P; Flint, H J (Plasmid, 2000)
Plasmid pJW1 from Selenomonas ruminantium subsp. lactilytica strain JW13 has been cloned in Escherichia coli vector pBluescriptSK(-) and completely sequenced. The plasmid is only 1410 bp with an overall GC content of 42.2%. Computer analysis of sequence data revealed a single open reading frame (ORF1, 146 amino acids, MW 16,525.5 Da) encoding a putative replication protein which is similar to the Rep protein of Ruminobacter amylophilus plasmid pRAO1. ORF1 is followed by a long AT-rich (75%) region and a region abundant in direct and inverted repeats. Comparison of DNA sequences revealed the presence of a short (<250 bp) DNA segment which is highly conserved between several small S. ruminantium plasmids including pJDB21.
Keywords: Sequence Analysis, DNA; plazmidy; sekvence aminokyselin; Conserved Sequence; sekvenční analýza DNA; sekvence nukleotidů; Molecular Sequence Data; molekulární sekvence - údaje; Amino Acid Sequence; Base Sequence; DNA, Bacterial; DNA bakterií; Plasmids; Selenomonas; konzervovaná sekvence